Čudovita pozornost na človeškost - Hedžet Tóth, Cvetka (Slavistična revija, 1997)
The paper discusses Kocbek's understanding of Ernst Bloch's philosophy, with particular emphasis on Kocbek's own response to the world, which has much in common with Bloch's. It is characteristic of both philosophers that they perceive man as a creature of hope and that they refuse pessimism and nihilism, evidently taking into account Marx's thought and Christian tradition. A reorientation towards man is motivated with the aspiration for happiness, which to Kocbek is a basis of the humanizing process. In his opinion,in more reent history this has even been leading to the uniformity of mankind.
Keywords: Bloch, Ernst, 1885-1977; ethics; etika; idejni nazori; Kocbek, Edvard, 1904-1981; nemška filozofija; Slovene literature; slovenska književnost; vplivi